Cloak and Dagger: Alternative Immune Evasion and Modulation Strategies of Poxviruses - Bidgood, Susanna R. (Viruses, 2015)
As all viruses rely on cellular factors throughout their replication cycle, to be successful they must evolve strategies to evade and/or manipulate the defence mechanisms employed by the host cell. In addition to their expression of a wide array of host modulatory factors, several recent studies have suggested that poxviruses may have evolved unique mechanisms to shunt or evade host detection. These potential mechanisms include mimicry of apoptotic bodies by mature virions (MVs), the use of viral sub-structures termed lateral bodies for the packaging and delivery of host modulators, and the formation of a second, “cloaked” form of infectious extracellular virus (EVs). Here we discuss these various strategies and how they may facilitate poxvirus immune evasion. Finally we propose a model for the exploitation of the cellular exosome pathway for the formation of EVs.